#1)
Answer:
y=2 and x=-7
Step-by-step explanation:
x-3y=-13
-x+4y=15
In this system, it would be recommended to use elimination because both x’s in the system can eliminate one another. After the eliminations of x, the system adds together the remainder of the system:
x-3y=-13
-x+4y=15
—————
(0)x+y=2 <-0x=0 so x has been eliminated.
y=2
Now, we have found y, so to find x, we will use substitution in one of the original equations. (It doesn’t matter which)
x-3y=-13
x-3(2)=-13 Solve for x.
x-6=-13
x=-7
#2)
Answer:
y=1 and x=5
Step-by-step explanation:
x=5y
3x-4y=11
This system probably would use substitution. The x value has already been given in terms of y(x=5y), so all that’s left to do is substitute x in the other equation(3x-4y=11).
Substitute:
3(5y)-4y=11
Solve for y:
15y-4=11
15y=15
y=1
Now that we have the value of y, we can substitute y in one of the original equations in the system to solve for x. (Doesn’t matter which equation).
x=5y
x=5(1)
x=5